Autonomic stress response of nurse students in an objective structured clinical examination (OSCE) (2021)
The aim of the present research was to analyze the autonomic stress response of nursing students in a nursing Objective Structured Clinical Evaluation (OSCE). We analyzed, in 41 s-year nursing degree students (20.1 ± 2.3 years), modifications in heart rate variability (HRV) to monitor the autonomic stress response before, during and after the 18 different scenarios of a complete OSCE. Heart rate mean response of nurse students was consistent with an anticipatory anxiety response at the beginning of the OSCE, showing a sympathetic nervous system activation, but HRV parameters show contradictory results. The most stressful OSCE station was the CPR maneuver, the stress response varying according to the station’s demands.